PENDIDIKAN KEWARGANEGARAAN DALAM KEHIDUPAN BERSOSIALISASI DAN MEMBANGUN KARAKTER BANGSA PADA SISWA SEKOLAH DASAR - Hamdani, Annisa Dwi; Dewi, Dinnie Anggraeni (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2021)
This study aims to provide an overview of the role of civic education in social life and building national character in elementary school students. The research method used is descriptive research based on the opinions of experts or previous research and collects data from several scientific journals, research results in the form of thesis, and other relevant sources. Citizenship education plays a very important role in social life and in building national character in elementary school students because it contains values, attitudes, morals, and norms or rules that can be used as guidelines in socializing and building national character. The implementation of the values, attitudes, morals, and norms contained in civic education is still not going well in the community so that it is necessary to inculcate these values more intensively so that the implementation and role of civic education in social life and building the character of this nation goes well.